Nobility, Respect and Horizontality as a Moral Foundation of Community in F. Nietzsche - Vázquez Manzano, Francisco (Res Publica. Revista de Historia de las Ideas Políticas, 2022)
In this paper I will carry out a hermeneutic work about political thinking of Friedrich Nietzsche, widely reviled in the early reception of his work, but revitalize by the way of news works about this aspect of his think. These works show the union between Nietzsche’s moral reflection and his approach for a community’s model. Nietzsche will be took as pretext in order to achieve a community’s characterization as «agonic community», which is founded in the permanent litigation and in the reciprocal affirmative recognition. This characterization of the community seeks keep away all individualism´s feature from her, showing all individualist obstinacy as sign of powerless and resentment.
Keywords: Nietzsche; Value; Community; Compensation; Litigation